Correlation Between Computed Tomography Severity Score and Mortality in Patients with COVID-19 Chest Infection - Sharma, Prakash; Lalchan, Subita; KC, Subash; Gyawali, Merina; Karki, Dipesh; Kushwaha, Niraj; Pun, Benju Tilija; Pokhrel, Amrit (Nepal Journal of Medical Sciences, 2021)
Introduction: Computed Tomography (CT) is one of the most essential diagnostic tools for early identification and treatment of COVID -19 pneumonia. The objective of this study was to identify the relationship between CT severity score and mortality in COVID-19 patients. Method: A total of 62 patients with confirmed COVID-19 were included in this study. All these patients underwent High resolution computed tomography (HRCT) chest using a standard protocol. The CT severity score in all of these patients was calculated and the results were analyzed by SPSS version 21. Results: A higher CT severity score was associated with higher chances of mortality in the patients of COVID-19. There was no significant association of mortality with the age, sex, and number of lobes involvement Conclusion: HRCT chest can help in the early identification of the patients who need to be admitted to the Intensive care unit. Early admission and intervention to patients with high CT severity scores can help to reduce mortality.